2012
DOI: 10.1371/journal.pone.0049366
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomotropic Properties of Weakly Basic Anticancer Agents Promote Cancer Cell Selectivity In Vitro

Abstract: Drug distribution in cells is a fundamentally important, yet often overlooked, variable in drug efficacy. Many weakly basic anticancer agents accumulate extensively in the acidic lysosomes of normal cells through ion trapping. Lysosomal trapping reduces the activity of anticancer drugs, since anticancer drug targets are often localized in the cell cytosol or nucleus. Some cancer cells have defective acidification of lysosomes, which causes a redistribution of trapped drugs from the lysosomes to the cytosol. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Despite this, the drug‐induced ELVP can be expected to significantly influence both the activity and pharmacokinetic behavior of the drug perpetrating the phenotype as well as those that may be subsequently administered. The degree to which a therapeutic drug is sequestered in lysosomes can influence its activity and selectivity by influencing the degree of binding interactions with intended therapeutic targets . In addition, the degree of drug accumulation in lysosomes can have a profound impact on the pharmacokinetics and distribution properties of drugs that are weakly basic and lysosomotropic .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, the drug‐induced ELVP can be expected to significantly influence both the activity and pharmacokinetic behavior of the drug perpetrating the phenotype as well as those that may be subsequently administered. The degree to which a therapeutic drug is sequestered in lysosomes can influence its activity and selectivity by influencing the degree of binding interactions with intended therapeutic targets . In addition, the degree of drug accumulation in lysosomes can have a profound impact on the pharmacokinetics and distribution properties of drugs that are weakly basic and lysosomotropic .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Golgi apparatus, early endosomes, and late endosomes are relatively acidic (∼pH 6.4, 6.2, 5.5, respectively) and would theoretically accumulate weakly basic compounds. In relation to these organelles however, the lysosomes would be subjected to the greatest ion‐trapping‐based accumulation of weakly basic compounds by virtue of their vastly more acidic luminal pH (4.0–4.5) . This hyperaccumulation of drugs within lysosomes can make their resident proteins, enzymes, and lipid bilayers particularly susceptible to drug‐induced alterations.…”
Section: Introductionmentioning
confidence: 99%
“…For drugs that are designed to target lysosomal proteins, medicinal chemists have imparted lysosomotropic properties to their drugs in an effort to improve potency . In addition, we have shown that it is possible to exploit lysosomal sequestration properties to increase the preferential toxicity of cancer drugs to cancer cells that possess a lysosomal acidification defect . Finally, the sequestration of drugs in lysosomes can have a profound impact on the pharmacokinetic properties of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 In addition, we have shown that it is possible to exploit lysosomal sequestration properties to increase the preferential toxicity of cancer drugs to cancer cells that possess a lysosomal acidification defect. 4,14,15 Finally, the sequestration of drugs in lysosomes can have a profound impact on the pharmacokinetic properties of drugs. Despite the fact that lysosomes typically only account for a small percentage of the total cell volume, the total cellular accumulation of most lysosomotropic drugs can be attributed to lysosomal sequestration.…”
Section: Introductionmentioning
confidence: 99%
“…There has been limited work carried out to overcome the problem of drug sequestration [109,116118]. One possible solution is to derivatize the amine group of the drug with a promoiety (e.g., to make an amide prodrug) so the amino group cannot be protonated or charged.…”
Section: Strategies For Improving Drug Transport Through the Biolomentioning
confidence: 99%